The Influence of Knowledge Management and Self Efficacy on Employee Performance with Job Satisfaction As A Variable Intervening At The Office Defense of Medan City - Affiza Elzera Chair Lubis; Ritha F. Dalimunthe; Yeni Absah (Outline Publisher, 2025)
The purpose of this study was to analyze the decline in employee performance in the form of decreased postal mail performance, analyze how employees can have high self-efficacy, analyze how employees are able to find the best solutions in dealing with problems and know knowledge management and job satisfaction. This type of research is causal with a quantitative approach. The population in this study were all employees of the Medan City National Land Agency, totaling 100 employees. Data collection methods used are using questionnaires, interviews and documentation studies. Methods of data analysis using descriptive statistical analysis and path analysis with the help of Smart PLS. The results of this study found that knowledge management had a positive and significant effect on employee performance. Self-efficacy has a positive and significant effect on employee performance. Knowledge management has a positive and significant effect on job satisfaction. Self-efficacy has a positive and significant effect on job satisfaction. Then indirectly job satisfaction is able to mediate the relationship between knowledge management and employee performance which has a positive and significant effect and job satisfaction is able to mediate the relationship between self-efficacy and employee performance which has a positive and significant effect on the Medan City National Land Agency.